Turning a Shove into a Nudge? : A 'Labeled Cash Transfer' for Education - Benhassine, Najy; Devoto, Florencia; Duflo, Esther; Dupas, Pascaline; Pouliquen, Victor (American Economic Association, 2016)
Conditional Cash Transfers (CCTs) have been shown to increase human capital investments, but their standard features make them expensive. We use a large randomized experiment in Morocco to estimate an alternative government-run program, a "labeled cash transfer" (LCT): a small cash transfer made to fathers of school-aged children in poor rural communities, not conditional on school attendance but explicitly labeled as an education support program. We document large gains in school participation. Adding conditionality and targeting mothers made almost no difference in our context. The program increased parents' belief that education was a worthwhile investment, a likely pathway for the results.